New Normal Public Education Adapting Activities During Pandemic - Purwanto, Purwanto (FORDICATE, 2021)
Education to the public during the Covid-19 pandemic is reallyneeded through the New Normal. Webinar as one of the media is very effectiveto reach all ages, both teenagers, adults, and parents. This activity presentsresource persons who are experts in the field of health to provideenlightenment. The committee consists of President University students and isguided by lecturers to ensure the activities go according to the expected plan.Online media such as Instagram, WhatsApp, and others are optimized to invitepotential participants. The results showed that the participants were veryenthusiastic in participating in the event through the zoom meeting. Deepcuriosity is evidenced by the many questions during the event. The entirecommittee, speakers and moderators are happy to answer one by one. Most ofthem get insight on how to deal with disasters and implement health protocolscorrectly. Fundraising was also part of the event, which was followed by thehanding over of donations to one of the orphanages in need at this time. Solidteamwork and effective communication have yielded satisfactory resultsalthough there is still a need for improvisation and innovation in the future.The further implication is that the sense of empathy and brotherhood willincrease when facing this serious calamity.